2018
DOI: 10.1177/0361198118792325
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the Interlayer Structural Response for Unbonded Concrete Overlays of Existing Concrete Pavements

Abstract: An improved mechanistic empirical design procedure for unbonded concrete overlays of existing concrete pavements (UBOLs) should account for the effect of the interlayer on the structural response of the pavement. One approach is to use the Totsky model to characterize the interlayer. The Totsky model treats the interlayer as a bed of springs between two plates and is currently incorporated into the rigid pavement finite element software ISLAB. A difficulty encountered in implementing this model is that there a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 1 publication
0
20
0
Order By: Relevance
“…With the growing interest in constructing thinner unbonded concrete overlays, several test sections have confirmed that there are limits of panel size versus slab thickness. The transition from asphalt-based interlayers to non-woven geotextile fabric interlayers throughout the U.S. has been paralleled in the design of the MnROAD UBOL test sections ( 46 ).…”
Section: Significant Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the growing interest in constructing thinner unbonded concrete overlays, several test sections have confirmed that there are limits of panel size versus slab thickness. The transition from asphalt-based interlayers to non-woven geotextile fabric interlayers throughout the U.S. has been paralleled in the design of the MnROAD UBOL test sections ( 46 ).…”
Section: Significant Contributionsmentioning
confidence: 99%
“…With a minimum collection frequency of four times per year, MnROAD test sections accumulate more falling weight deflectometer (FWD) data than any other concrete pavement in the U.S. This testing frequency allows for the characterization of seasonal effects on FWD pavement responses that has been useful to the development of modern mechanical-empirical designs ( 44 , 46 ). MnROAD has also contributed toward the next generation of pavement condition devices, such as the rolling weight deflection vehicles and has hosted multiple FHWA calibration events, in which pavement management vehicles can be evaluated equally at one facility on a variety of pavement sections and surface textures ( 47 ).…”
Section: Significant Contributionsmentioning
confidence: 99%
“…and 425 psi/in. for a fabric interlayer (8). The next step in developing the FEM model was validation using the established Totsky k-values.…”
Section: Model Validationmentioning
confidence: 99%
“…These networks are separated into loaded or unloaded slab, axle type, joint depth, and temperature. Because of symmetry of the temperature loading condition, only one ANN is developed for both the loaded and unloaded sides of the joint ( 25 ). Each of the ANNs with each of their predictors are shown in Equations 3–5.…”
Section: Predictive Modelmentioning
confidence: 99%